Coronavirus Disease 2019 and Skin: A Retrospective Analysis - Bhagyashree Babanrao Supekar; Vaishali Hainath Wankhade; Shraddha P Kote; Shirin Sunil Gawali; Apoorva Dhananjay Chopkar; Rajesh P Singh; Arpit Govinda Dhakate (Wolters Kluwer Medknow Publications, 2024)
Introduction: Coronavirus disease 2019 (COVID-19), a unique viral infection causing multiorgan failure, can lead to diverse dermatological manifestations, unlike other viral exanthems. There is a scarcity of Indian literature describing these manifestations. Aims and Objectives: To study the dermatological manifestations due to COVID-19 infection. Materials and Methods: It was a retrospective analysis (6 month) of patients with dermatological manifestations related to COVID-19 infection. Medical records were evaluated with respect to demography, detailed clinical presentations, real-time reverse transcription-polymerase chain reaction/rapid antigen test positivity, and related investigations. Statistical Analysis: It was done using proportion, mean, and percentages. Results: A total of 76 cases were recruited. Out of the 76 COVID-19-related cases, there were 67 diagnosed and 9 suspected cases (later came positive). The overall female predominance (n = 69) was observed. The most common age affected was 31-40 years. The most common presentation during prodromal, acute, and postacute phases was urticaria. Other manifestations were chilblain-like, varicella-like, pityriasis rosea-like, erythema multiforme-like, petechial rash, multisystemic inflammatory syndrome in children and confirmed cases of mucormycosis seen with cutaneous manifestation. Conclusion: Our study highlights the need for severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) testing in patients presenting with rash in otherwise asymptomatic individuals having contact with confirmed case and when associated with systemic symptoms. Dermatological manifestations may play an important role in identifying cases early and serve as an important proxy in managing further spread of this disease in the midst of the global pandemic. Urticaria with fever has diagnostic significance since this combination can be a symptom of an otherwise not confirmed SARS-CoV-2 infection.